Zakat as a Local Revenue in Aceh: A Dynamics of Policy Implementation in the Local Realm - Dahlawi Dahlawi; Saddam Rassanjani; Herizal Herizal (IAIN Manado, 2021)
The legitimacy given by the central government to Aceh through Law Number 11 of 2006 concerning the Aceh Government has resulted in a policy of managing Zakat as a source of regional income in Aceh by Baitul Mal Aceh (BMA). Qanun Number 10 of 2018 concerning Baitul Mal is the basis for realizing these ideals. This research tries to look at the dynamics of policy implementation in the local realm using George C. Edwards III's theory. The authors apply qualitative research to get the desired conclusion by observing and interviewing several respondents, especially those implementing the policy. In implementing Qanun Number 10 of 2018, Baitul Mal has experienced many obstacles; zakat management as local revenue cannot be implemented according to sharia regulations but must follow regional financial management guidelines. Therefore, it is necessary to make further adjustments to qanuns or derivative legal rules to make their management more optimal and follow Syar'i provisions.